Criteria for peanut seed pre-conditioning for the tetrazolium test - Bittencourt, S. R.M. [UNESP]; Vieira, R. D. [UNESP]; Rodrigues, T. J.D. [UNESP] (My University, 1997)
The staining pattern of peanut (Arachis hypogaea L.) seeds with a tetrazolium solution was evaluated to determine the adequate conditions of seed quality evaluations. Three seed lots with different vigour levels and similar moisture content were pre-conditioned using the combination of five periods of time (4, 8, 12, 16 and 20 hours) and four temperatures (20, 25, 30 and 35°C) and then exposed to a 1.0% tetrazolium solution for three hours. The moisture content levels of seeds conditioned for 8 hours at the temperatures of 25, 30 or 35°C, for 12 hours at 20 or 25°C and for 16 hours at 20°C, were above 30%. In this range of moisture level, the staining in tetrazolium was clear and uniform, reflecting an appropriate conditioning of the seeds. However, under a practical point of view, the period of 16 hours at 20°C showed to be the best option, since it allows to start the pre-conditioning on late afternoon of one day and submit the seeds for staining in the following morning.